NON-ENGLISH STUDENTS’ PERCEPTIONS ON THE USE OF SOCIAL MEDIA FOR LEARNING ENGLISH DURING COVID-19 PANDEMIC - Zahrotul Mufidah (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2022)
Abstract: This study aims to determine the Non-English students’ perceptions on the use of social media for learning English during covid-19 pandemic. Non English students are students who are not registered in the English department and take English lesson as general compulsory subject. In this study, the researcher used qualitative approach with a descriptive qualitative design. The participants of this research were 30 students of fourth semester students’ who have completed the English subject. The participants are from Indonesian Language and Literature Education Department and Mathematic Education Department in University of Islam Malang. From the two study programs, researcher only choose one class of each study program. To know the non-English students’ perceptions on the use of social media for learning English during covid-19 pandemic, an online-based questionnaire and an online-based interview were used as the methods of collecting the data. The finding showed that non-English students had positive perceptions about social media. From the results of the questionnaire, non-English students chose YouTube, TikTok, Instagram, Twitter, and WhatsApp as social media to learn English during the pandemic. They said that social media provides various sources for learning English, these students can use social media to study anywhere and anytime. This situation makes them relaxed and motivated to study English more actively. Non-English students also mentioned some of the challenges when using social media, namely network connection problems, inappropriate content or advertisements that distract them from focusing on studying. In addition, this research was conducted online during pandemic. Therefore, it is suggested for future researchers to investigate students’ perception on the use of social media for learning English to conduct face-to-face research to get detailed results. Key Words: Non-English Stundents, Social Media, Learning English